Rancang Bangun Model Audit Manajemen Sumber Daya Manusia, Menggunakan Pendekatan Sistem - Willy Susilo; - Eriyatno; M. Joko Affandi; D. Agus Goenawan (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2011)
The purpose of this study is to design an audit model for Human Resource Management (HRM), using soft system methodology (SSM). The study was conducted in two stages. The first stage is  designing an audit model, using  Strategic Assumption Surfacing and Testing (SAST), and Interpretative Structural Modeling (ISM), through Focus Group Discussion (FGD). The SAST  technique was used, involving some experts through FGD, for identification and ranking  of assumptions of the HRM audit model. The ISM technique was used to identify the relationship between elements and structure of the HRM audit program. The second stage was verification of the model through a trial audit, which was done in two phases. The first phase  was  establishment of  FGD, involving some senior/managerial staff  to prepare  a set of customized audit devices (questionair, techniques, etc), with reference of the designed model of HRM audit. The second phase  was application of developed assessment devices by the respondents. The selected topic for the trial audit was corporate culture. The approaches used in the  trial audit were self assessment, importance-performance analysis (IPA) and perception survey. The output of this study is a model of HRM audit for application in a manufacturing company. This study has a limitation, because both the design and verification processes involved experts only from one company respectively, and the trial audit was done partially.  The output of this study therefore shall have to be further verified  if   the model is to be applied extensively in other types of organization,  like government bodies and  non-commercial sectors. The preposition of this study, that  application of the audit model resulted from this study  will enhance the effectiveness of HRM and eventually enhance the effectiveness of organization, has been proven  to be  partially true. The perception survey of the model  users (n=30),  indicated  the means  of:  importance (3.8),  usefulness ( 4.3), practicality( 3.2), feasibility (3),  dan recommendation (4).